Graphene quantum dot membranes as fluorescent sensing platforms for Cr (VI) detection. (November 2016) - Carrasco, Pedro M; García, Ignacio; Yate, Luis; Tena Zaera, Ramón; Cabañero, Germán; Grande, Hans J.; Ruiz, Virginia
Abstract: A simple and versatile method to produce filtration membranes with graphene quantum dots (GQD) and their excellent performance as turn-off fluorescence sensing platforms for Cr (VI) detection in water is presented. Suitably functionalized GQD were immobilized on various types of membranes (nylon, cellulose and glass fiber) and the resulting GQD-modified membranes exhibited the characteristic fluorescence fingerprint of the GQD probes. The membrane fluorescence was quenched by highly toxic Cr (VI) ions due to selective coordination to GQD functional groups. The analytical performance of membranes was comparable to that of dispersed GQD fluorescent probes, displaying a fast and linear response to Cr (VI) concentration in the 1–500 μM range, a low detection limit of 190 nM, high sensitivity, reproducibility and selectivity. Moreover, the membranes can be regenerated by simple washing with deionized water and reused, preserving their good sensing response after several Cr (VI) detection-washing cycles. Membrane sensing performance was very stable after being immersed in water for several days and filtering water through them. Graphical abstract: